The implementation of new minister of religion of Brunei, Indonesia, Malaysia, and Singapore criteria towards the Hijri calendar unification - Mufid, Abdul (HTS teologiese studies, 2023)
This study aims to integrate hadith, astronomy and sociology studies in examining the implementation of Hijri calendar unification through a multidisciplinary approach. The Hijri calendar is based on the astronomical phenomena of the earth-moon-sun system and should refer to the provisions of Islamic law or fiqh to be implemented in worship. For the preparation of a good Hijri calendar, agreement on criteria, date line, and authority is necessary. Furthermore, agreement on criteria requires a valid argument based on astronomical studies. An agreement on the implementing region boundaries is necessary due to the round earth and the hilal [crescent moon] cannot be observed simultaneously anywhere. It is also needed to resolve unavoidable differences, specifically in the appearance of the hilal and in schools of Islamic law. The problems to be solved are as follows: What is the strategy for implementing Hijri calendar unification? This study is based on a review of hadith and fiqh literature, analysis of astronomical data related to criteria, and experiences of Indonesia and Islamic countries regarding the Hijri calendar unification. The results show that implementing the Hijri calendar unification through the three approaches above can be carried out and accelerated.Contribution: This study contributes to showing the results of a multidisciplinary approach in the problem of implementation of the new Ministers of Religious Affairs of Brunei Darussalam, Indonesia, Malaysia, and Singapore (MABIMS) criteria towards unification of the Hijri calendar.